An account of epistemic democracy: ignorant majorities and the better decision - Scarborough, Mark L. (2015)
This thesis analyses traditional and contemporary democratic theory from an epistemic, instrumental angle. It argues that these theories depend too heavily on intrinsic values, such as equality of participation, which then sacrifice good decision outcomes. Using a reverse-contractarian tool, where social contracts can be prospective rather than retrospective, it is possible to argue that a free public would form government on the basis of services it provides and ergo, instrumental reasons. As such, legitimate decisions are those that are based upon an evidential diagnosis of a problem, and use evidence to help bring about the good provision of such problem-solving services. It uses the observation of topic-specific ignorant majorities, defined as being where each citizen has both areas of expertise and areas of ignorance, to criticise both fair-proceduralist accounts and non-democratic technocratic accounts. The former overstates the contribution that every citizen can have when designing and managing those services, whereas the latter understates the broader contribution knowledgeable minorities can have in governance. Overall, a tailored democracy is called for using the name service democracy, which is a theoretical response to the above observations. It concludes by offering epistemic policy proposals that could be implemented within the current governmental institutions and policy processes. It calls for state-funding of political parties to avoid undue influence over policy, committee oversight of ministerial appointments so that competence can be assessed and finally academic and professional crowd-sourcing to allow the wider knowledgeable minority in a given area to contribute to policy creation and development.